Modelling Climate-based changes of sugarcane growing areas in Western Kenya - Kigen, Charles; Makindi, Stanley Maingi; Masibayi, Edward N; Agevi, Humphrey; Odira, Zedekiah; Muyekho, Francis (My University, 2016)
Sugar cane (Saccharum spp. hybrids) is an important cash crop for Kenya’s sugar industry contributing significantly to the country’s economy through farming and employment. Its production in Kenya is both irrigation and weather dependent. In Western Kenya, it is a major economic activity heavily dependent by more than 50% of the population. To plan for sustainable development of the counties in western Kenya, it is important to understand how the anticipated climate change will influence this cash crop. This paper modeled the potential sugarcane growing areas of current and the year 2050 climatic periods. The sugarcane location data were extracted using fishnet from published materials while climate data was obtained from world climate database website. Data analysis and modeling was done using Maxent and DIVA-GIS softwares. The model generated an excellent Area Under Curve of 0.996 and more than 0.6 suitability level areas increased by 167.21% in 2050 climatic period. The main variables contributing more than 5% of change in suitability areas are Precipitation of Driest Period (42%), Precipitation of Coldest Quarter (28.8%), Isothermality (13.3%) and Precipitation of Wettest Quarter (8.1%). The generated information will guide the policy makers and stakeholders in making informed decisions with regard to the efforts of promotion of sugarcane production in western Kenya Counties
Keywords: Sugarcane; Maxent; DIVA-GIS; modeling